Modelling the impact of strategic planning, structural capital, relational capital, members’ participation, governance practices and human capital development on cooperatives’ performance / Mahazril ‘Aini Yaacob ...[et al.] - Yaacob, Mahazril ‘Aini; Hammad Ahmad Khan, Hafizah; Yaacob, Zuraini; Aminuddin, Adnan (Institute of Research Management & Innovation (IRMI), 2013)
The cooperative society plays a significant role towards the economic development in Malaysia. It was first established in 1922 to protect the welfare of rural people and has expanded its establishment since then. With the aims to help its members, it is said that cooperatives need to accelerate its performance. However, there are issues regarding its weaknesses, especially in management, financial, and members' participation. Therefore, this study aims to identify the factors influencing its performance through strategic planning, structural capital, relational capital, members’ participation, governance practices, and human capital development. Questionnaires constructed are distributed among 72 cooperatives board members listed under the 100 best cooperatives in Malaysia for the year 2011. By using Pearson's correlation, Factor Analysis and Multiple Regression Analysis, this study found that the relational capital play: a vital role in exerting a positive influence on the cooperatives’ performance. It is suggested that the cooperatives should always be involved in all the activities organized by the Suruhanjaya Koperasi Malaysia so that it can promote the 1 product and services provided to the society as a whole. This would improve the networking of the cooperatives with the government, suppliers, and customers, which indirectly would give a positive influence on its performance. This finding will provide a guidance for the cooperative to improve its shortcomings performance towards realizing the National Cooperative Policy 2011-2020